Prolonged Viability of Senecavirus A in Exposed House Flies (Musca domestica) - Justin Heath Turner; Willian Pinto Paim; Mayara Fernanda Maggioli; Cristina Mendes Peter; Robert Miknis; Justin Talley; Fernando Vicosa Bauermann (Viruses, 2022)
House flies (Musca domestica) are often present in swine farms worldwide. These flies utilize animal secretions and waste as a food source. House flies may harbor and transport microbes and pathogens acting as mechanical vectors for diseases. Senecavirus A (SVA) infection in pigs occurs via oronasal route, and animals shed high virus titers to the environment. Additionally, SVA possesses increased environmental resistance. Due to these reasons, we investigated the tenacity of SVA in house flies. Five groups of flies, each composed of ten females and ten males, were exposed to SVA, titer of 109.3 tissue culture infectious dose (TCID50/mL). Groups of male and female flies were collected at 0, 6, 12, 24, and 48 h post-exposure. For comparison purposes, groups of flies were exposed to Swinepox virus (SwPV). Infectious SVA was identified in all tested groups. Successful isolation of SVA demonstrated the titers varied between 106.8 and 102.8 TCID50/mL in female groups and varied from 105.85 to 103.8 TCID50/mL in male groups. In contrast, infectious SwPV was only detected in the female group at 6 h. The significant SVA infectious titer for prolonged periods of time, up to 48 h, indicates a potential role of flies in SVA transmission.